Stability of finger millet genotypes under diverse environments - Sood, Salej; Patro, T. S. S. K.; Karad, Sunil; Sao, Abhinav (The Indian Journal of Genetics and Plant Breeding, 2016)
The present study aimed at deciphering the stability and patterns of genotype × environment interaction (GEI) in finger millet genotypes tested in All India Coordinated Trials using GGE biplot technique. The combined ANOVA for grain yield of five finger millet cultivars at four environments showed that environments (E), genotypes (G) and GEI were highly significant (P